Tindak Pidana Informasi Elektronik Dalam Kerangka Hukum Positif - Rio Armanda Agustian; Jeanne Darc Noviayanti Manik (PROGRESIF: Jurnal Hukum, 2021)
Act No. 11 of 2008 on Information and Electronic Transactions is the first Act in the field of information technology and electronic transactions as a product of much-needed legislation and has become the spearhead that lays the groundwork for regulation in the field of technology utilization, although now during the implementation of the ITE Act experienced some problems regarding legal certainty about criminal provisions after the decision Constitutional Court, protection personal data and criminal investigation. Method in this study is normative juridical with a statutory and conceptual approach. Government supports the development of IT through its legal infrastructure and arrangements so that the use of IT is carried out safely to prevent its misuse by paying attention to the religious and socio-cultural values of Indonesian people. Side of protection and legal certainty in the use of information technology, media, and communication in order to develop optimally. Protection of personal data in conducting activities in cyberspace can be the right to enjoy a private life and free from all kinds of interference, right to be able to communicate with others without the act of spying and right to supervise access to information about one's personal life and data.